Making time time and management in modern organizations - Whipp, Richard; Adam, Barbara; Sabelis, Ida, 1954- (Oxford University Press, 2002)
Time is often taken for granted in daily life and the business world. The aim of this book is to bring time into sharper focus and in particular to look at the way time is constructed, made, managed, and used in organizations. The book both provides an overview of some of the key concepts in time and it explores how particular features of the modern world extend and change the temporal dimension of organizational activity. - ;Time is an essential feature of social and organizational life and part of the deep structure of business activity. Plans, performance, productivity, and pay are all link.
Keywords: Time management.; Industrial management.; elektronické knihy; electronic books